Throughput evaluation for the downlink scenario of co-tier interference in heterogeneous network - Mohammad Kamrul, Hasan; Ahmad Fadil, Ismail; Hassan Abdalla Hashim, Aisha; Wahidah, Hashim (Asian Research Publishing Network (ARPN), 2015)
To extend the coverage and capacity of Heterogeneous Networks (HetNets), femtocells (HeNodeBs) has been impressive to deploy in in-house or apartment. Owing to co-channel spectrum involvement these HeNodeB sources Co-Tier interference (CTI) with neighbor HeNodeBs and users of HeNodeB (HUE) in orthogonal frequency division multiplexing Access (OFDMA). As a result, CTI is occurred which causes of system throughput degradation. This paperinvestigates the OFDMA subcarrier allocation techniques and algorithms. A Genetic Algorithm based SubcarrierAllocation (GA-SA) framework is evaluated to enhanced throughput of HeNodeB and HUE. The enhancement of the system throughput and Signal to Interference Noise Ratio (SINR) is analyzed to mitigate CTI. The system level simulation is considered to evaluate the performance of the framework. The results show that the throughput is enhanced for HUE and HeNodeB, which can mitigate the CTI in OFDMA.